Pengembangan Sistem Informasi Pendaftaran Santri Baru Berbasis Website Menggunakan Metode Addie Studi Kasus : Pondok Pesantren Sandar Madinatul Athfal Petanahan Kebumen - Siti Nurhidayah; Endang Wahyuningsih (Yayasan Literasi Sains Indonesia, 2025)
Technological developments have updated the way to access information, including in the Islamic boarding school environment. The Sandar Madinatul Athfal Islamic Boarding School in Kebumen, which has been using a manual student registration system, faces various obstacles such as inefficiency, recording errors, and lack of online information. To overcome this, a student registration information system website was developed. The research was conducted from September 2024 to January 2025.”The data was obtained based on the results of observations at the Sandar Madinatul Athfal Petanahan Islamic Boarding School, Kebumen, interviews with students who manage the administration of the boarding school, literature studies, and also the results of filling out questionnaires. The method to develop the system is ADDIE which is a sequential stage from Analysis, Design, Development, and Implementation to Evaluation. Evaluation is done through functional testing (BlackBox Testing) and filling out questionnaires to 10 users, with an average score of 35.3 which was included in the